Legitimasi Berlapis dan Negosiasi Dinamis pada Pembayaran Perkawinan Perspektif Pluralisme Hukum - Wardatun, Atun (Al-Ahkam, 2018)
This article is based on an ethnographic study that uses participatory observation of eight marriage payment negotiations in the city of Mataram, West Nusatenggara. It argues that the marriage payment in the Muslim tradition of Sasak in the city of Mataram is based on strong legal pluralism or a variety of equally strong laws in which no single legal system dominates and is subordinated to each other. Furthermore, this research sheds light on extending meaning of legal pluralism in which it may include dialogue between the same legal system eg between different customary laws. This strong model of legal pluralism is seen in two ways. First, the layered legitimacy of Sasak marriage by using many models of marriage payments, namely religious payment in the form of mahr for marriage validity, local payment in the form of pisuke and ajikrama for social appropriateness, and state payment in the form of administrative costs for formal legality. Second, the dynamic negotiation between customary law holders concerning the marriage payment when inter-ethnicity marriage occurs (exogamy), where different traditions can absorb each other. The argument at the same time debates the view that has placed the three legal systems: Islam, adat (customs), and the state as opposed and subordinate to each other.